Expand the following ( x – 2y + 3z) ki power 2​

Question

Expand the following
( x – 2y + 3z) ki power 2​

in progress 0
Parker 2 months 2021-11-23T02:14:00+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-11-23T02:15:17+00:00

    Step-by-step explanation:

    (x-2y+3z)^2

    we use the identity that is

    (x+y+z)^2=x^2+y^2+z^2+2xy+2yz+2zx

    = (x)^2+(-2y)^2+(3z)^2+2(x)(-2y)+2(-2y)(3z)+2(x)(3z)

    = x^2+4y^2+9z^2-4xy-12yz+6xz.

    I think u Understand the answer.

    0
    2021-11-23T02:15:44+00:00

    Answer:

    Step-by-step explanation:

    (x-2y+3z)^2 =

    x^2 +(-2y)^2 +(3z)^2 +(2×x×_2y) +(2×_2y×3z) +(2×3z×x)

    =x^2+4y^2+9z^2_4xy -12yz+6xz

    Please mark me as brainlist

    By:Tolety Roshan

Leave an answer

Browse

14:4+1-6*5-7*14:3+5 = ? ( )